Novel compound heterozygous mutations of LAMA2-limb–girdle muscular dystrophy: A case report and literature review - Wang, Duo-Zi; Li, Bing-Hu; Ma, Qiong; Yu, Zhou; Chen, Kai; He, Ying; Tan, Song (Frontiers in Neurology, 2023)
Laminin α2 (LAMA2) gene pathogenic variants can lead to limb-girdle muscular dystrophy (known as LGMDR23), which is relatively rare reported and characterized by proximal weakness of the limbs. We present the case of a 52-year-old female who developed weakness of both lower extremities gradually since the age of 32. MRI brain showed symmetrical sphenoid wings like white matter demyelination in bilateral lateral ventricles. Electromyography showed bilateral lower extremity quadriceps muscle damage. Next-generation sequencing (NGS) found two loci variations in the LAMA2 gene: c.2749+2dup and c.8689C>T. This case highlights the importance of considering LGMDR23 in patient presenting with weakness and white matter demyelination on MRI brain and further expands the gene variants spectrum of LGMDR23.